Prenatal ultrasound heating impacts on fluctuations in haematological analysis of Oryctolagus cuniculus - Ahmad Zaiki, Farah Wahida; Md Dom, Sulaiman; Abdul Razak, Hairil Rashmizal; Hassan, Hamzah Fansuri (2013)
Prenatal Ultrasound (US) is commonly used as a routine procedure on pregnant women. It is generally perceived as a safe procedure due to the use of non-ionizing radiation. However, the neurotoxicity of diagnostic prenatal US was detected to have a correlation with high susceptibility to early developing fetus. This research involved in vivo experimental model by using 3rd trimester pregnant Oryctolagus cuniculus and exposing them to US exposures for 30, 60, and 90 minutes at their gestational day (GD) 28-29. The output power and intensities, spatial peak temporal average intensity (ISPTA) of US were varied from 0.4 to 0.7 W and 0.13 to 0.19 W/cm2 respectively were tested initially in free-field, water. Haematological analysis was carried out to detect any changes in blood constituents. Statistically significant differences were detected in red blood cell (RBC) count (P<0.001), haemoglobin (Hb) concentration (P<0.001) and also platelet (PLT) count (P<0.001) in newborn of Oryctolagus cuniculus. These findings indicate the possibility of US heating in causing defects on studied animal.